Clay Mortar Performance Improvement by Modifying the Physical Characteristics of Wheat Straw. (2016) - Andres, Dana Maria; Manea, Daniela Lucia; Fechete, Radu; Jumate, Elena
Abstract: Wheat straw is a waste in agriculture, which most often are burnt in the fields, thus contributing to higher emissions of carbon dioxide. Clay-based plaster began to win over the specialists because of the advantages it presents and that are natural materials, environmentally friendly. The aim of this study is to find a way to improve the mechanical characteristics of plaster based of clay with wheat straw, by saturating straws before placing them in mortars, considering the results obtained in a previous study. The study's objective is to increase mechanical resistance on plaster based on clay with wheat straw. Due to high water absorption capacity of straw, straw saturation was proposed prior to their introduction into the mix. We studied how saturated straw influenced the mechanical characteristics of mortars.